Cheek tooth repulsion aided by computer-assisted surgery in 16 equids - Klopfenstein Bregger, Micaël D.; de Preux, Mathieu; Brünisholz, Hervé P.; Van der Vekens, Elke; Schweizer, Daniela; Koch, Christoph (Frontiers in Veterinary Science, 2025)
This retrospective case series reports on the use of computer-assisted surgery (CAS) to perform cheek tooth repulsion in 16 equids. Thirteen of the 16 subjects in this case series had a mandibular cheek tooth repulsed, and 3 had a maxillary cheek tooth removed. Surgery was performed on all subjects under general anesthesia, and all but one were placed in lateral recumbency. All cheek teeth were successfully removed by navigated repulsion, except in one case where additional intraoral sectioning was performed. In one horse, a surgical approach through the contralateral nasal conchae was made to facilitate exodontia. This led to considerable hemorrhage and a temporary tracheotomy was performed to ensure airway patency postoperatively. Six subjects needed at least one additional revision surgery to remove either osseous or dental fragments or sequestrated alveolar bone. Outcome was successful in all but one subject, which was euthanized after surgery because a squamous cell carcinoma was diagnosed histologically. The real-time intraoperative guidance provided by CAS allows for controlled and accurate surgical access to targeted dental structures and exodontia of cheek teeth.